Pengaruh Komunikasi Persuasif dalam Penyuluhan Produksi Pangan Industri Rumah Tangga terhadap Perubahan Sikap Para Usaha Kecil Menengah (UKM) di Kota Bogor - Maria Fitriah; Ike Atikah Ratnamulyani (Jurnal Komunikasi Pembangunan, 2015)
The purposes of this research: (1) to analyse persuasive communication Bogor City Health Office in counseling Household Food Production Industry, (2) to analyse  change of attitude the Small and Medium Enterprises (UKM) Bogor City, (3) designing persuasive communication to change attitudes the Small and Medium Enterprises (UKM) Bogor City, (4) to analyse the effect of persuasive communication Bogor City Health Office to change attitudes the Small and Medium Enterprises (UKM) Bogor City. This research conducting in Bogor City Health Office area on May 2015. Population of its research is around the Small and Medium Enterprises (UKM) Bogor City community. Sample of research the pain according random sampling amount 30 respondens. Collecting data conducted by observation, questioner, interview, and documentation study. Data analyses by spearman correlation with SPSS program.             Based on research result, persuasive Communication in Extension Food Safety Household Industrial Production has good category, changes in the attitude of the domestic industry has a very good category, the influence of persuasive communication Bogor City Health Department to change the attitude of the Small and Medium Enterprises with a correlation value of 0.494 and interpretation of the correlation coefficient being, design of persuasive communication to change attitudes , namely the existence of elements that include credibility communicator, attractions, and power as well as the elements of a message that includes the concept and format of messages that cause a change in attitude.keyword: persuasive communication , education , attitude change